(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The development of science greatly depends upon experimentation to reveal the mysteries of nature and to confirm the previous innovations. In the field of research, though experimental studies provide better understanding regarding the efficacy, mode and site of action of the drugs, but the evaluation of the drug is incomplete unless and until they are tried clinically. Clinical study is the essence of any research work. It reveals the promises and pitfalls of any hypothesis. It further rectifies the hypothesis and improves its practical applicability. Acharyas have emphasized on the need for a physician to be well versed in the theory as well as the practical. Thus, it is mandatory for a good physician to be well versed in both, the theory and the practical. The major aim of treatment of this disease is to provide relief from pain and discomfort, prevention of further disease progress, loss of joint function, maintenance of productive and active life without hampering of routine activities as they are chiefly affected. Cervical Spondylosis has a great impact on social, occupational, and other functioning areas of the individual. The modern medical science is still not having a definite curative treatment for this disease. Although, Analgesics, NSAIDs and Corticosteroids are being used for symptomatic management but their role in curing the disease is very limited rather the patients get addicted for the particular drug. In such a scenario, there is a need for the efficient management of Cervical Spondylosis in a natural way with fewer / no side effects and less cost. In this study, the clinical trial was carried out on Manyastambha (Cervical Spondylosis) and an attempt had been made to manage it through Ayurveda with the help of Patra Pinda Sweda & Nadi Sweda.